Recent advances on the regulation of bacterial biofilm formation by herbal medicines - Zhang, Meimei; Han, Wenyu; Gu, Jingmin; Qiu, Cao; Jiang, Qiujie; Dong, Jianbao; Lei, Liancheng; Li, Fengyang (Frontiers in Microbiology, 2022)
Biofilm formation is a fundamental part of life cycles of bacteria which affects various aspects of bacterial-host interactions including the development of drug resistance and chronic infections. In clinical settings, biofilm-related infections are becoming increasingly difficult to treat due to tolerance to antibiotics. Bacterial biofilm formation is regulated by different external and internal factors, among which quorum sensing (QS) signals and nucleotide-based second messengers play important roles. In recent years, different kinds of anti-biofilm agents have been discovered, among which are the Chinese herbal medicines (CHMs). CHMs or traditional Chinese medicines (TCMs) have long been utilized to combat various diseases around the world and many of them have the ability to inhibit, impair or decrease bacterial biofilm formation either through regulation of bacterial QS system or nucleotide-based second messengers. In this review, we describe the research progresses of different chemical classes of CHMs on the regulation of bacterial biofilm formation. Though the molecular mechanisms on the regulation of bacterial biofilm formation by CHMs have not been fully understood and there are still a lot of work that need to be performed, these studies contribute to the development of effective biofilm inhibitors and will provide a novel treatment strategy to control biofilm-related infections.